We Probably Thought That Would Be True: Perceiving Complex Emotional States in Nonhumans - Pierotti, Raymond; Annett, Cynthia (Ethnobiology Letters, 2014)
Review of: Do Fish Feel Pain? Victoria Braithwaite. 2010. Oxford University Press, New York. Pp. 256. 35.00 (hardcover). ISBN 9780199551200. How Animals Grieve. Barbara J. King. 2013. University of Chicago Press, Chicago. Pp. 208, 7 halftones. 25.00 (cloth). ISBN 9780226436944.